“My Whole Life I’ve Been a Fraud”: Resisting Excessive (Self-)Critique and Reaffirming Authenticity as Communal in David Foster Wallace’s “Good Old Neon” and Albert Camus’s The Fall - Allard den Dulk (Humanities, 2023)
The themes of paralyzing, solipsistic self-critique versus the necessarily communal character of authentic, meaningful existence in the work of American novelist David Foster Wallace are best understood in light of existentialism. This article compares Wallace’s story “Good Old Neon” with Albert Camus’s novella The Fall, as responses to similar unproductive tendencies within the respective postmodernist and Marxist discourses of their times. Both works portray an absolutist self-critique that produces feelings of (inauthentic) fraudulence and exceptionality; and both include an interlocutor that ultimately makes the reader the direct addressee of the text. In doing so, “Good Old Neon” and The Fall confront the reader with the moral task of resisting excessive (self-)critique and reaffirming authentic, meaningful existence as always arising in connection to others.